THE ROLE OF CITIZENS' RIGHTS AND OBLIGATIONS IN REALIZING NATIONAL AND STATE LIFE - Bambang Yuniarto; Manda Ameliyah; Hani Hanifah; Nadine Lidya Putri; Laura Florencia Azahra Gunalan; Farhan Nurrurakhman (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The rights and obligations of citizens are fundamental aspects in realizing a harmonious, just, and democratic national and state life. However, in practice, imbalances in understanding and implementation are still frequently found, both by individuals and state institutions. This study aims to analyze the role of citizens' rights and obligations in maintaining national stability and encouraging active public participation, particularly within the context of Pancasila values and the provisions of the 1945 Constitution. The research questions include how rights and obligations function in state life and how their implementation occurs in current social reality. This study employs a literature review method with a descriptive-qualitative approach through content analysis of various constitutional documents, civic education literature, and relevant academic research. The results indicate that the fulfillment of citizens' rights plays a crucial role in ensuring social justice, legal protection, and public participation in the democratic system. Meanwhile, the implementation of obligations, such as obeying the law and participating in state defense, contributes to maintaining social order, security, and national unity. The study concludes that a balance between rights and obligations is a primary prerequisite for realizing a dignified and prosperous nation, thus necessitating the strengthening of civic literacy and the enforcement of just laws.